The observable supernova rate in galaxy–galaxy lensing systems with the TESS satellite. Issue 1 (13th May 2021) - Holwerda, B W; Knabel, S; Steele, R C; Strolger, L; Kielkopf, J; Jacques, A; Roemer, W
ABSTRACT: The Transiting Exoplanet Survey Satellite ( TESS ) is the latest observational effort to find exoplanets and map bright transient optical phenomena. Supernovae (SNe) are particularly interesting as cosmological standard candles for cosmological distance measures. The limiting magnitude of TESS strongly constrains SN detection to the very nearby Universe ( m ∼ 19, z < 0.05). We explore the possibility that more distant SNe that are gravitationally lensed and magnified by a foreground galaxy can be detected by TESS, an opportunity to measure the time delay between light paths and constrain the Hubble constant independently. We estimate the rate of occurrence of such systems, assuming reasonable distributions of magnification, host dust attenuation, and redshift. There are approximately 16 Type Ia SNe (SNIa) and 43 core-collapse SNe (SNcc) expected to be observable with TESS each year, which translates to 18 and 43 per cent chance of detection per year, respectively. Monitoring the largest collections of known strong galaxy–galaxy lenses from Petrillo et al., this translates into 0.6 and 1.3 per cent chances of an SNIa and an SNcc per year. The TESS all-sky detection rates are lower than those of the Zwicky Transient Facility and Vera Rubin Observatory. However, on the ecliptic poles, TESS performs almost as well as its all-sky search, thanks to its continuous coverage: 2 and 4 per cent chance of an observed SN (Ia or cc) each year. These rates argue for timely processing of full-frame TESS imaging to facilitate follow-up and should motivate further searches for low-redshift lensing system.